Perceived Employability Variations Across Specializations Subjects in the Faculty of Education at Tribhuvan University (Pragyaratna प्रज्ञारत्न, 2024)
This study explores the level of perceived employability among education students, examining the multifaceted dimensions of skills and competencies crucial for success in the professional realm. Employability extends beyond technical proficiency, encompassing a range of attributes contributing to adaptability and effectiveness. Perceived employability, a subjective assessment of one's ability to secure and maintain employment, plays a pivotal role in shaping individuals' career approaches. A quantitative and exploratory approach was employed, utilising a cross-sectional survey and questionnaire within the context of Nepal's Faculty of Education at Tribhuvan University. The study involved 271 final-year students, employing proportional random sampling and statistical analyses. While education students express high confidence in various employability dimensions, a nuanced categorisation reveals a dual nature of 'presence' and 'consolidation' levels across competencies. Furthermore, specialisation subjects significantly influence perceived employability, with science majors showing higher levels. The study underscores the imperative for a comprehensive understanding of employability factors, emphasising the substantial impact of major subject choice on education students' confidence and readiness for future careers. The findings provide insights for academic institutions, policymakers, and students to enhance strategies for bridging the gap between education and employability in the Nepalese context.